The Impact of Educational Investment on the Growth and Welfare of Medan Society - Fajriawati, Fajriawati (Jurnal Riset Ilmu Pendidikan, 2025)
This study analyzes the effect of education investment on economic growth and public welfare in Medan City in the period 2019-2024. With an empirical qualitative approach, this study uses survey, interview, and observation methods involving 300 respondents from various levels of society. The results of the analysis show that education investment has a positive correlation with economic growth and increasing public welfare. Education investment contributes 45% to economic growth and 52% to public welfare in Medan. The main factors that play a role in this relationship include increased labor productivity, technological innovation, and wider access to economic opportunities. In addition, this study highlights the importance of inclusive and sustainable education policies in driving economic development. The conclusion of this study confirms that improving the quality of education can be an effective strategy in reducing social disparities and improving overall public welfare.